Awareness Regarding Breast Cancer, Perceptions and Compliance towards Mammography among Women Visiting Tertiary Care Hospitals in Rawalpindi - Hisam, Aliya; Mashhadi, Syed Fawad; Fatima, Aliha; Saleem, Remsha; Naseer, Muhammad Awais; Tariq, Hafiz Aleem; Shahid, Muhammad Irfan (Pakistan Armed Forces Medical Journal, 2024)
Objective: To find out awareness about breast cancer, perceptions and compliance towards mammography in women reporting to tertiary care hospitals in Rawalpindi.Study Design: Descriptive cross-sectional study.Place and Duration of Study: Tertiary care hospitals in Rawalpindi Pakistan, from Nov 2021 to Apr 2022.Methodology: A sample size of 120 women was calculated. Sampling technique was non-probability convenient sampling. The data collection tool consisted of demographic information, questions to assess awareness, perceptions and compliance towards mammography. Data were entered and analyzed in SPSS version 26.Results: The survey was administered to 120 women in tertiary care hospital. The study showed that majority of population was well-aware of breast cancer. Out of 120, 104(86%) women believed that new breast masses should be evaluated at clinics.According to 113(94%) women breast cancer can be cured and 95(79.2%) had belief that breast cancer can be prevented. Fortyfour (36.6%) women were non-complaint towards mammography having higher barrier scores. There was high significance of occupation (p